The Quest for Status and R&D-based Growth - Klaus Prettner; Franz Hof (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analyze the impact of status preferences on technological progress and long-run economic growth. For this purpose, we extend the standard relative wealth approach by allowing the two components of the representative household's wealth, physical capital and shares, to differ with respect to their status relevance. Relative wealth preferences imply that the effective rate of return of saving in the form of a particular asset is the sum of its market rate of return and its status-related extra return. It is shown that the status relevance of shares is of crucial importance: First, an increase in the intensity of the quest for status raises the steady-state economic growth rate only if the status-related extra return of shares is strictly positive. Second, for any given degree of status consciousness, the long-run economic growth rate depends positively on the relative status relevance of shares. Third, while in the standard model the decentralized long-run economic growth rate is less than its socially optimal counterpart, the wealth externalities in our model counterbalance this distortion to some extent provided that shares matter for status.
Keywords: D31; O30; O10; 330